Investigation and Modeling of Biogas Production Potential from Urban and Fruit Juice Wastewater Treatment Plant Sludge through Pretreatment - Esin Hande Bayrak Işık (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effect of pretreatments applied to the sewage sludge of the Tokat Municipality wastewater treatment plant (WTP), the sewage sludge of the packaged wastewater treatment plant (PWTP) of a fruit juice production plant, and the aqueous phases of their mixtures on biogas production was investigated. Chemical, thermal (microwave (MW) and hot plate (HP)) and chemical-thermal pretreatments were applied to these sludge samples. Considering the results in all samples, the highest biogas production amount and efficiency were found in the pre-biogas-unit aqueous phase of the sewage sludge of the Tokat WTP, which was applied 20% H2SO4+10-minute (min) thermal MW pretreatment, with 667.51 ml and 396.34 ml biogas/g water dissolved SM value, respectively. Statistical analyses included the Duncan comparison test for cumulative biogas production efficiencies at the end of 65 days and the maximum exponential increase function and Gompertz equations for cumulative biogas amounts. Accordingly, the most appropriate model was tried to be determined. The electricity generated at the end of the 22-day incubation period at the facility meets 36% of the electricity needed by the Tokat WTP. At the end of the experimental studies (20% H2SO4+10 min thermal MW pretreatment), it can be said according to the 22-day biogas data that the biogas production efficiency increased by 3.41 times, this would meet all the electricity needed by the facility, and that there would be an extra 23% electricity generation of the total generation. Mixing and using fruit juice PWTP and WTP treatment sludge in the production of biogas will enable both the utilization of this waste in biogas production and the weakening and reduction of high parameter values, which sometimes cause problems in the sludge discharged from the Tokat WTP due to urban wastewater treatment, to acceptable limits.